Flexure Behaviour of Corroded Reinforcement Concrete Beams Under Sustained Loads - Abed Al-Mortadha O.; Daud Sultan A. (Civil and Environmental Engineering)
The long-term behaviour of concrete beams with corroded reinforcement is a critical aspect that demands thorough comprehension to ensure the serviceability and durability of reinforced concrete structures. This paper aims to investigate the long-term performance of reinforced concrete (RC) beams with corroded reinforcement numerically. Two experimental datasets from existing literature were selected to build a nonlinear finite element model. The selected beams were tested under four-points sustained bending load and three bending point flexural test with deferent level of corrosion. A parametric study was then conducted taking into account concrete compressive strength, reinforcement yield strength, ambient temperature, relative humidity and sustained load level to get a better understanding on the factors that effecting the long-term behaviour of concrete beams with corroded reinforcement. Results demonstrated that, Diana FEA has an excellent ability to predicating the long-term behaviour of RC beams with corroded reinforcement. The analysis of the parametric study revealed that increasing relative humidity from 70% to 90% resulted in a 45% to 53% reduction in developed deflections. Whereas once the temperature rose from 20°C to 40°C the developed deflection increased from 13.9% to 17.2%. This outcome demonstrating the significant impact of environmental factors on the long-term behaviour of corroded reinforced concrete beams. Finaly, once the yiled stregth of the steel reinforcement increased from 380 Mpa to 550 Mpa, the developed deflection rate increased from 46% to 54%.